1986
DOI: 10.1152/jappl.1986.60.4.1407
|View full text |Cite
|
Sign up to set email alerts
|

Low acute hypoxic ventilatory response and hypoxic depression in acute altitude sickness

Abstract: Persons with acute altitude sickness hypoventilate at high altitude compared with persons without symptoms. We hypothesized that their hypoventilation was due to low initial hypoxic ventilatory responsiveness, combined with subsequent blunting of ventilation by hypocapnia and/or prolonged hypoxia. To test this hypothesis, we compared eight subjects with histories of acute altitude sickness with four subjects who had been asymptomatic during prior altitude exposure. At a simulated altitude of 4,800 m, the eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 0 publications
7
82
1
Order By: Relevance
“…In a study by BARTSCH et al [8], subjects with AMS revealed a transient decrease in isocapnic hypoxic ventilatory response (but neither in poikilocapnic hypoxic nor hypercapnic ventilatory response) within 4 h after arrival at 4,559 m, whereas this was not observed in controls. No differences in isocapnic and poikilocapnic hypoxic, and in hypercapnic ventilatory responses were present among AMS and control subjects at low altitude, and after they had spent a night at 4,559 m. A low ventilatory response to hypoxia has also been observed in subjects experiencing symptoms of AMS during short-term exposure to 4,800 m in a hypobaric chamber over up to 7 h [10]. Thus, subjects prone to AMS may have an initial relative hypoventilation within hours after rapid ascent to high altitude.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a study by BARTSCH et al [8], subjects with AMS revealed a transient decrease in isocapnic hypoxic ventilatory response (but neither in poikilocapnic hypoxic nor hypercapnic ventilatory response) within 4 h after arrival at 4,559 m, whereas this was not observed in controls. No differences in isocapnic and poikilocapnic hypoxic, and in hypercapnic ventilatory responses were present among AMS and control subjects at low altitude, and after they had spent a night at 4,559 m. A low ventilatory response to hypoxia has also been observed in subjects experiencing symptoms of AMS during short-term exposure to 4,800 m in a hypobaric chamber over up to 7 h [10]. Thus, subjects prone to AMS may have an initial relative hypoventilation within hours after rapid ascent to high altitude.…”
Section: Discussionmentioning
confidence: 76%
“…Hypoxia seems to play an important role [3,6,7]. A reduced ventilatory response to hypoxia, and impaired pulmonary gas exchange related to pulmonary fluid accumulation, and water and salt retention have been implicated in development of exaggerated hypoxemia in subjects with AMS [8][9][10]. As AMS often develops or worsens over the night, when periodic breathing and repetitive oxygen desaturation are also prevalent, a causal relationship or a common pathophysiological pathway have been evaluated [11,12].…”
mentioning
confidence: 99%
“…First, there is a variable degree of susceptibility to acute mountain sickness in the current subjects. Others have shown that individuals not susceptible to acute mountain sickness have a higher HVR than those who are susceptible to acute mountain sickness [28] or to HAPE [8]. If only subjects without a history of severe acute mountain sickness from the control group were compared with HAPE-susceptible subjects, HVR was almost significantly lower (p50.07) in HAPE-susceptible subjects.…”
Section: Pulmonary Vascular Responsementioning
confidence: 94%
“…In two previous studies (King and Robinson 1972;Moore et al 1986), it was determined that individual differences in ventilatory sensitivities were related to differences in ventilation and AMS symptomatology during subsequent hypobaric exposures. The conclusions derived from these "successful" studies clearly disagree with our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that have directly related pre-altitude ventilatory sensitivities to AMS utilized small numbers of subjects whose data were either selected for analyses after their illness had occurred (King and Robinson 1972) or whose subjects were selected based on prior knowledge that they would or would not get sick (Moore et al 1986). It has not been determined if it is possible t-preselect a subgroup of individuals who are likely to get sick at moderate altitudes froln a larger group of individuals whose susceptibility to AMS is unknown using the results of ventilatory sensitivity tests conducted at low altitudes prior to deployment.…”
Section: Introductionmentioning
confidence: 99%